Outcomes of critically ill solid organ transplant patients with COVID‐19 in the United States. Issue 11 (15th September 2020) - Molnar, Miklos Z.; Bhalla, Anshul; Azhar, Ambreen; Tsujita, Makoto; Talwar, Manish; Balaraman, Vasanthi; Sodhi, Amik; Kadaria, Dipen; Eason, James D.; Hayek, Salim S.; Coca, Steven G.; Shaefi, Shahzad; et al.
Abstract : National data on patient characteristics, treatment, and outcomes of critically ill coronavirus disease 2019 (COVID‐19) solid organ transplant (SOT) patients are limited. We analyzed data from a multicenter cohort study of adults with laboratory‐confirmed COVID‐19 admitted to intensive care units (ICUs) at 68 hospitals across the United States from March 4 to May 8, 2020. From 4153 patients, we created a propensity score matched cohort of 386 patients, including 98 SOT patients and 288 non‐SOT patients. We used a binomial generalized linear model (log‐binomial model) to examine the association of SOT status with death and other clinical outcomes. Among the 386 patients, the median age was 60 years, 72% were male, and 41% were black. Death within 28 days of ICU admission was similar in SOT and non‐SOT patients (40% and 43%, respectively; relative risk [RR] 0.92; 95% confidence interval [CI]: 0.70‐1.22). Other outcomes and requirement for organ support including receipt of mechanical ventilation, development of acute respiratory distress syndrome, and receipt of vasopressors were also similar between groups. There was a trend toward higher risk of acute kidney injury requiring renal replacement therapy in SOT vs. non‐SOT patients (37% vs. 27%; RR [95% CI]: 1.34 [0.97‐1.85]). Death and organ support requirement were similar between SOT and non‐SOT critically ill patients with COVID‐19. Abstract : Solid organ transplant recipients with critical SARS‐CoV‐2 infection have a similar risk of death, acute respiratory distress syndrome, and requirement for organ support as nonsolid organ transplant patients.